Effect of upward seepage on bedload transport rate - Liu, Xiao-Xie (2015)
The paper presents an investigation of injection effects on the bedload transport rate. According to dimensional analysis, two dimensionless groups, an Einstein’s parameter group and a modified densimetric Froude number group, were chosen to examine how injection affects the bedload transport rate. Experimental studies were conducted in an open-channel flume with an upward seepage zone. The sediment particles used for the test were 0.9 mm in diameter. The experimental results show that an increase in the injection velocity causes a reduction in the shear velocity excess, which is defined as the difference between the shear and critical shear velocities, leading to a reduction in the bedload transport rate. The equation for predicting the bedload transport rate in the presence of upward seepage was derived empirically. The proposed prediction method is suitable for engineering practice, since it only requires the undisturbed flow condition, properties of sediment particles, and the injection velocity.